The Association of Immune Cell Infiltration with Metastasis Location in De Novo Metastatic Triple Negative Breast Cancer: A Multicenter Cross-Sectional Study in Indonesia - Jeffry Beta Tenggara; Andhika Rachman; Joedo Prihartono; Lisnawati Lisnawati; Sonar Soni Panigoro; Didik Setyo Heriyanto; Ricci Steven; Kevin Tandarto; Samuel Juanputra; Aru Wisaksono Sudoyo (Acta Medica Indonesiana, 2024)
Background: Triple-negative breast cancer (TNBC) is an aggressive cancer subtype, with limited treatments and a high metastasis risk. The varying location of metastasis in TNBC patients often leads to in prognosis in breast cancer. Therefore, this study aimed to investigate the potential association between immune cells profiles in the tumor microenvironment and metastatic patterns. Methods: We conducted a multicenter cross-sectional study in 2022 to examine formalin-fixed paraffin-embedded (FFPE) and medical record data from 2015 to 2020 in de novo metastatic TNBC patients. The medical records provided crucial information about the sites of metastasis. Immunohistochemistry (IHC) analysis was carried out on primary breast tumor tissues to evaluate the expressions of cluster of differentiation (CD)4 T-cells, CD8 T-cells, CD163, FOXP3 Tregs, and programmed death-ligand 1 (PD-L1), along with immune cells ratios showing antitumor-to-protumor activity (CD4/FOXP3, CD8/FOXP3, CD4/CD163, CD8/CD163). Metastatic locations were grouped into bone-only, visceral, lung, liver, and brain metastasis.  Results: A total of 120 metastatic TNBC patients were documented for their metastatic location and IHC report. The clinical and histopathological characteristics showed that the majority of the patients were within the 40-65 years old group, and 34.2% had standard body mass index (BMI). Furthermore, the majority (89.22%) of the patients showed No Special Type (NST), (56.7%) had histopathology grade III, high Ki-67 ≥20% (85.8%), and positive PD-L1 expression (30.8%), with visceral metastasis indicating the highest proportion of 75.8%. Patients with a high CD8/FOXP3 and CD4/FOXP3 ratio were significantly prone to have bone-only metastasis compared to visceral metastasis (p= 0.028 and p=0.024, respectively).  Conclusion: The ratio of antitumor to protumor T-lymphocytes had a significant relevance in the metastatic location patterns in TNBC.